Abortion - a philosophical perspective - MN Jali (AOSIS, 2001)
The central issue in the abortion debate is the moral status of the conceptus. There are two positions that argue this issue. At one extreme are the views of the pro-life group which argues that human life begins at the moment of conception whilst at the other are views of the pro-choice group that argues in favour of a woman's right to self-determination. Two basic principles come into conflict in this debate, namely the Value of Life and that of Self-determination. In this paper the arguments forwarded by each group in justification of its position are presented. Also discussed is the moderate developmental viewpoint which accepts that the genetic basis of an individual is established at conception. Some development, however, has to occur before the conceptus can be called a person. The fact that an entity is a potential person is a prima facie reason for not destroying it. On the other hand, we need not conclude that a person has a right to life by virtue of that potentiality. Simultaneously we should recognise that the right a potential entity has, may be nullified by the woman's right to self-determination.